Development of a 31P magnetic resonance spectroscopy technique to quantify NADH and NAD+ at 3 T - Mevenkamp, Julian; Bruls, Yvonne M. H.; Mancilla, Rodrigo; Grevendonk, Lotte; Wildberger, Joachim E.; Brouwers, Kim; Hesselink, Matthijs K. C.; Schrauwen, Patrick; Hoeks, Joris; Houtkooper, Riekelt H.; Buitinga, Mijke; de Graaf, Robin A.; et al. (Nature communications, 2024)
NADH and NAD + act as electron donors and acceptors and NAD + was shown to stimulate mitochondrial biogenesis and metabolic health. We here develop a non-invasive Phosphorous Magnetic Resonance Spectroscopy ( 31 P-MRS) method to quantify these metabolites in human skeletal muscle on a clinical 3 T MRI scanner. This new MR-sequence enables NADH and NAD+ quantification by suppressing α-ATP signal, normally overlapping with NADH and NAD + . The sequence is based on a double spin echo in combination with a modified z-Filter achieving strong α-ATP suppression with little effect on NAD + and NADH. Here we test and validate it in phantoms and in humans by measuring reproducibility and detecting a physiological decrease in NAD + and increase in NADH induced by ischemia. Furthermore, the 31 P-MRS outcomes are compared to analysis in biopsies. Additionally, we show higher NAD + and lower NADH content in physically active older adults compared to sedentary individuals, reflecting increased metabolic health. NADH and NAD+ act as electron donors and acceptors and NAD+ was shown to stimulate mitochondrial biogenesis and metabolic health. Here, the researchers developed and validated a non-invasive Phosphorous Magnetic Resonance Spectroscopy method to non-invasively quantify NAD+ and NADH in muscle on a clinical 3 T MRI scanner.